INTEGRATING ISLAMIC VALUES INTO THE DEVELOPMENT OF PROGRESSIVE ACTION UNIT OF THE EIGHTH-GRADE STUDENT AT MTs MADANI PAO-PAO - Rahmawati,; Kamsinah,; Rahman, Indah Fadhilah; Muthi'ah, (English Language, Linguistics, and Culture International Journal, 2022)
This research aims at integrating Islamic Values into English material especially in basic competences 3.8 and 4.8 about Progressive Action for the eighth grade students at MTs Madani Pao-Pao based on 2013 curriculum. Based on the preliminary study, the researcher found that the textbook that is used at school is too general and still far from the term integrated with Islamic values. The research design used in this study was Research and Development (R&D). The development model used was ADDIE model. It consists of need analysis, design, development, implementation, and evaluation. The procedures included analyzing materials needed by distributing questionnaire to the students and analyzing the basic competences used, designing a blueprint of materials, and developing the English materials through ADDIE model. In this research, the expert was involved in order to validate the product. There were three systematic aspects that they validated of the product: the aspect of the content/material, the aspect of learning and the aspect of graphics feasibility. Therefore, the result indicated that based on experts judgment as well as product development result, the developed basic competences 3.8 and 4.8 was applicable to be taught at the eighth grade students of Junior High School as topics in English for them.